The Voters Behavior Towards Women Candidates in the 2019 Legislative Election in North Luwu Regency - Ananda Rezky Wibowo (Journal of Social Science, 2021)
The results showed that the absence of female candidates who passed the legislative body in North Luwu Regency showed that the implementation of the policy affirmative action of the 30 percent quota of women's representation was not optimal, even though voter behavior was no longer significant in questioning gender issues in politics. This is due to the dominance of male political elites which still have a big influence because the voting community still sees the existence of these political elites. In addition, it is due to the failure of political parties to regenerate and build political commitment to women. Although in the 2014-2019 period there were two female representatives in the legislative body of North Luwu Regency, in the 2019-2023 elections they were not re-elected because they no longer had a network of power and kinship. The most crucial factor is that money politics is still a compromise tool in the electoral process, political actors play a role in money politics, so this makes no female candidates elected because of their inability to compete with the flow of money politics even though they have incurred political costs. which is not the least. Voters will choose a certain candidate if he feels there is a reciprocal that will be accepted as well as political candidates who are afraid of losing their votes, this irrational act (playing money politics) becomes the last resort.